Fish Protein Hydrolysate as Protein Enrichment in Texture-Modified Salmon Products - Leena Prabhu; Aase Vorre Skuland; Paula Varela; Jan Thomas Rosnes (Foods)
The aim of this study was to develop a chilled, texture-modified salmon product for dysphagia patients, enriched with dairy and fish hydrolysate proteins. The challenge was to create a product with appealing sensory qualities and texture that meets level 5 (minced & moist) of the IDDSI framework. Atlantic salmon (Salmo salar) was heat-treated (95 °C/15 min), blended, and reconstructed by adding texture modifiers, casein and whey protein, and enzymatically derived fish hydrolysate. The products were packaged in oxygen-free plastic trays, heat-treated to a core temperature of 95 °C for 15 min, chilled and stored at 4 °C for 29 days and analyzed for microbiology, instrumental texture, and sensory properties. The texture analyses showed that products with fish protein hydrolysate were softer than those only with casein and whey protein, a result also confirmed by the IDDSI fork pressure test. Quantitative descriptive analysis of salmon products revealed significant differences (p < 0.05) in sensory attributes within flavour (fish flavour), and texture (softness and adhesiveness) but there was no significant change in bitterness. The shelf-life study at 4 °C showed good microbiological quality of the product, and safety after 29 days with appealing sensory and textural properties, i.e., a product at IDDSI level 5 for age care facilities and commercial production was obtained.